Self-compassion training to improve spiritual well-being for teachers at a Catholic elementary school in Surabaya City - Stefany Livia Prajogo; Putu Nitya Sarahdevina (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Training activities were carried out for teachers at one of the Catholic elementary schools in Surabaya. Based on the results of the needs analysis that was carried out, it was found that teachers had problems at the level of spiritual well-being. Spiritual well-being is essential for each individual personally. Moreover, as teachers in Catholic schools, they emphasize character education for their students. Therefore, teachers are given an intervention through self-compassion training to improve their spiritual well-being. The results of this training show an increase in the level of spiritual well-being, both qualitatively and quantitatively. Kegiatan pelatihan dilakukan kepada para guru di salah satu SD Katolik di Kota Surabaya. Berdasarkan hasil analisis kebutuhan yang telah dilakukan, didapatkan hasil bahwa para guru memiliki masalah pada tingkat kesejahteraan spiritual. Padahal, kesejahteraan spiritual sangat penting dimiliki oleh tiap individu secara personal. Terlebih lagi, dalam profesi mereka sebagai guru di Sekolah Katolik yang menekankan pada pendidikan karakter untuk peserta didiknya. Oleh karena itu, para guru diberikan sebuah intervensi berupa pelatihan self-compassion untuk meningkatkan kesejahteraan spiritualnya. Hasil dari pelatihan ini menunjukkan adanya peningkatan pada tingkat kesejahteraan spiritual, baik secara kualitatif maupun kuantitatif.